Cadaveric organ donation in China: A crossroads for ethics and sociocultural factors. Issue 10 (March 2018) - Wu, Yijin; Elliott, Robert; Li, Linzi; Yang, Tongwei; Bai, Yusen; Ma, Wen
Abstract : Abstract: In this paper, we will discuss several ethical issues concerning cadaveric organ donation from the perspective of sociocultural factors that are unique to China under the condition that China has ended the use of executed prisoner's organs for transplants. It is found that though great developments have been made in organ transplantation, the ethical issues relating to organ transplantation still face dilemmas in China. It is argued that organ donation and transplantation in China could make further progress if the ethical issues proposed in this paper can be carefully considered.